ANALISIS PENGARUH FISHING EFFORT (UPAYA TANGKAP) TERHADAP PROFITABILITAS PADA KELOMPOK USAHA PERIKANAN TANGKAP PURSE SEINE DI KABUPATEN SERAM BAGIAN BARAT - Evracia Turukay (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
WPP (Fisheries Production Area) Seram for all new fish species is utilized 30% to 40% and specifically for small pelagic potential in Kab. SBB has only been used 3.8% which shows that there are still opportunities to be developed. Fishing Effort or capture effort in SBB which greatly determines the output of Purse Seine capture fisheries business is Running Cost (Sea Cost), Shore Cost (Landing Cost), Number of crew members, and Sea Time.Based on the Proposive Sampling method, 30 business groups were established whose data was taken for 2 consecutive years (2013 - 2014) so that the number of samples became 60 samples. The business groups are spread in Kairatu Barat Sub-district, West Seram District, Huamual Sub-District, Rear Haamual Sub-District, and Kec. Manipa Islands. This research is a Quantitative Descriptive study, where ROA (Return On Assets) to calculate the ability of Assets to generate profits, and Multiple Regression to determine the effect of variables - independent variables on the dependent variable partially.The results showed that Running Cost had a positive and significant effect on Profitability (ROA) which proved the waters of KabBB were still under Exploited for small pelagic fish, then Shore Cost had a negative and significant effect on Profitability (ROA) which illustrates that Fishing Based Distance to the target market is quite an obstacle, and the variable number of ABK does not affect profitability (ROA) which indicates that the number of catches is not only determined by the number of crew members related to the size of the net but also determined by the skills and abilities of the crew. . And finally the Sea Time variable has a negative and significant effect on Profitability (ROA) which is a description that the distance to go home to Fishing Ground needs to be considered carefully. Keywords: Running Cost, Shore Cost, Number of crew members, Sea Time, and Profitability (ROA)